Escalating progression of mental health disorders during the COVID-19 pandemic: Evidence from a nationwide survey. - Li Ping Wong; Haridah Alias; Afiqah Alyaa Md Fuzi; Intan Sofia Omar; Azmawaty Mohamad Nor; Maw Pin Tan; Diana Lea Baranovich; Che Zarrina Saari; Sareena Hanim Hamzah; Ku Wing Cheong; Chiew Hwa Poon; Vimala Ramoo; et al. (PLoS ONE, 2021)
Since the first nationwide movement control order was implemented on 18 March 2020 in Malaysia to contain the coronavirus disease 2019 (COVID-19) outbreak, to what extent the uncertainty and continuous containment measures have imposed psychological burdens on the population is unknown. This study aimed to measure the level of mental health of the Malaysian public approximately 2 months after the pandemic's onset. Between 12 May and 5 September 2020, an anonymous online survey was conducted. The target group included all members of the Malaysian population aged 18 years and above. The Depression Anxiety Stress Scale (DASS-21) was used to assess mental health. There were increased depressive, anxiety and stress symptoms throughout the study period, with the depression rates showing the greatest increase. During the end of the data collection period (4 August-5 September 2020), there were high percentages of reported depressive (59.2%) and anxiety (55.1%) symptoms compared with stress (30.6%) symptoms. Perceived health status was the strongest significant predictor for depressive and anxiety symptoms. Individuals with a poorer health perception had higher odds of developing depression (odds ratio [OR] = 5.68; 95% confidence interval [CI] 3.81-8.47) and anxiety (OR = 3.50; 95%CI 2.37-5.17) compared with those with a higher health perception. By demographics, young people-particularly students, females and people with poor financial conditions-were more vulnerable to mental health symptoms. These findings provide an urgent call for increased attention to detect and provide intervention strategies to combat the increasing rate of mental health problems in the ongoing COVID-19 pandemic.